Using applied palaeoecology and participatory system dynamics modelling to investigate changes in ecosystem services in response to climate and social-ecological drivers within the middle berg river catchment, South Africa - Dirk, Cherié Janine (Department of Biological Sciences, 2022)
Conservation and agricultural landscapes are social-ecological systems that co-produce ecosystem services, which change over time in response to environmental, biotic and social drivers. Failure to consider this variability, and the feedbacks that cause system instability, can have consequences for sustainable ecosystem services provision. A transdisciplinary approach is needed to understand the interacting processes that drive the dynamics of ecosystem service provision. This study applies a conceptual meta-framework: past-present-future lens of environmental change to interpret changes in land cover and ecosystem services, with the aim of informing sustainable land-use management within the Cape Floristic Region, a globally recognised biodiversity hotspot. The project methodology followed a four-part structure: (1) Changes in land cover, fire, herbivory, and hydrological indicators were reconstructed using palaeoecological proxies (fossil pollen, charcoal, coprophilous spores, geochemistry, and diatoms) from two sites and associated sedimentary cores. (2) Palaeoecological data were interpreted in terms of supporting/provisioning (plant biodiversity) and regulating (water quality and soil erosion regulation) services, and (3) the drivers of these changes (climate, fire and herbivory) were analysed. (4) A pilot study used participatory system dynamics modelling to articulate dynamic feedbacks and explore future scenarios. Palaeoecological and modelling results explored resilience and thresholds in ecosystem services, defined the historical range of variability and was used to generate management recommendations. Results showed that (1) high temporal resolution, multi-proxy data suggested variability in ecosystem services. (2) Ecosystem change was driven mainly by climate in the early palaeo-records with increasing anthropogenic influence from the mid-20th C, and (3) although some plant biodiversity and landscape heterogeneity was lost, the main vegetation elements remain, suggesting no environmental thresholds have yet been crossed. (4) Even so, model simulation results show that it may be difficult to return to past ecological states. Adaptive grazing-fire management is recommended to maintain and restore ecosystem function, thereby decreasing the likelihood of future regime shifts to a degraded alternative stable state. This innovative interdisciplinary approach provides a contextual understanding of processes that influence dynamic social-ecological systems and translates long-term data into a form that can be used by policymakers and land-use managers to inform sustainable management of ecosystem services.